Effcient synthesis of nanosized zeolite Y utilizing gradual heating: post‑synthesis modifcation and their catalytic performance in propylene oligomerization (2025)
ABSTRACT: Producing nanosized zeolites Y has been restricted to a Si/Al ratio lower than 2.0, requiring prolonged crystallization periods. This study employed temperature ramps during nucleation and crystallization to synthesize nanosized zeolites Y with a Si/Alratio of 2.4, ranging from 47 to 100 nm, in just one day. Sequential post-synthesis desilication and dealumination treatments were used to modify the pore structure and acidity of the zeolites, leading to hierarchical zeolite formation. These modifcations enhanced the structural stability and porosity of the zeolites while preserving their high crystallinity. Desilicated zeolites, unlike dealuminated ones, possessed straighter and more uniform mesoporous within their crystals, with diameters smaller than 5 nm. Additionally, successive desilication produced a greater number of intracrystalline mesoporous. The solids obtained from both processes exhibited porosity within the zeolite structure connected to the external surface, poten- tially improving the mass transfer limitations of the original zeolite due to the lack of mesoporous. Catalysts were prepared using modifed nanozeolites for evaluation in the propylene oligomerization reaction. Catalysts based on dealuminated and desilicated nanosized zeolite Y showed high conversions above 20%, especially for dealuminated zeolites with conversions of 50%. Additionally, the catalysts demonstrated selectivity towards hydrocarbons in the C5-C7 range, suggesting better diffusion and access of propylene molecules to the active sites, favoring the formation of medium-sized hydrocarbon fractions. Conversely, the formation of longer hydrocarbon chains (C12+) was not favored, possibly due to insufcient mesoporous for larger molecule difusion and a distribution of acid sites that encourages the union of longer hydrocarbon chains.